Effects Of Some Climatic Factors On Soil Moisture In Scots Pine Stands With Different Crown Closure - Aydın, Miraç; Hınıs, Adem Sinan (Kastamonu University, 2024)
In this study, the effects of climate factors on soil moisture in Scots Pine stands with different crown closure were investigated. As a result of the study, it was revealed whether soil moisture values differ in Scots Pine stands in the same aspect, depth and slope group. The effects of some climate elements (air temperature, air humidity and rainfall) on the soil moisture values in the areas where the Scots Pine in different crown closures were investigated. We took 6 different forest plots in the same depth, slope and aspect group. The average soil moisture values was found 23.91% in Open forest plot (POF), 26.84% in P1 plot (Low crown closure scots pine stand), 16.72% in P2 (Medium crown closure scots pine stand), 16.00% in P3 (Full crown closure scots pine stand), 30.79% in Simulation plot (PS) and 28.62% in Erosion plot (PE). It was determined that the lowest average soil moisture values were found in the P2 and P3 plots and the highest soil moisture values were in the PS and PE plots.
Keywords: Climatology; Soil Moisture; Scots Pine; Crown Closure; Land Use; Physical Geography; İklim Bilimi; Toprak Nemi; Sarıçam; Kapalılık; Arazi kullanımı; Fiziki Coğrafya; 15. Life on land